ChemInform Abstract: Popping of Graphite Oxide: Application in Preparing Metal Nanoparticle Catalysts. Issue 42 (October 2015) - Gao, Yongjun; Chen, Xi; Zhang, Jiaguang; Asakura, Hiroyuki; Tanaka, Tsunehiro; Teramura, Kentaro; Ma, Ding; Yan, Ning
Abstract A popcorn‐like transformation of graphite oxide (GO; obtained by a modified Hummers method) into large‐volume graphene oxide sheets (PGO) is achieved by heating differently oxidized graphite granules (quartz tube, 190‐200 °C, 30‐60 sec).